2020
DOI: 10.1002/adfm.202002448
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Shot Mesoporous Silica Rods Scaffold for Induction of Humoral Responses Against Small Antigens

Abstract: Vaccines have shown significant promise in eliciting protective and therapeutic responses. However, most effective vaccines require several booster shots, and it is challenging to generate responses against synthetic molecules and peptides often used to increase target specificity and improve vaccine stability. As continuous antigen uptake and processing by antigen‐presenting cells and persistent toll‐like receptor priming can amplify humoral immunity, it is explored whether a single injection of a mesoporous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 53 publications
3
52
0
Order By: Relevance
“…All gel formulations displayed solid‐like properties and robust yield stresses as well as a large dependence of the viscosity on the shear rate. This high degree of shear‐thinning, coupled with rapid recover of the mechanical properties following shear, enable facile injectability 14,15 . These mechanical properties demonstrate that the PNP hydrogels yield under the high pressure delivered by syringe injections and flow smoothly through the needle into the subcutaneous space, where the materials rapidly reforms into a solid‐like depot for extended cargo delivery.…”
Section: Discussionmentioning
confidence: 92%
“…All gel formulations displayed solid‐like properties and robust yield stresses as well as a large dependence of the viscosity on the shear rate. This high degree of shear‐thinning, coupled with rapid recover of the mechanical properties following shear, enable facile injectability 14,15 . These mechanical properties demonstrate that the PNP hydrogels yield under the high pressure delivered by syringe injections and flow smoothly through the needle into the subcutaneous space, where the materials rapidly reforms into a solid‐like depot for extended cargo delivery.…”
Section: Discussionmentioning
confidence: 92%
“…These materials provide tools to direct the immune response by attracting endogenous cells to the vaccine site, increasing antigen uptake and providing activation cues locally and rapidly 135 . Various materials have been explored for the formation of a local inflammatory niche to enhance immune responses 136 ; however, the impact of specific niche properties (for example, specific innate cell populations and/or their activation profiles) and the duration of niche persistence on downstream vaccine responses are poorly understood. Studies with self-assembled scaffolds based on silica rods have indicated that the local inflammatory niche must persist for at least 7 days to achieve prolonged antibody titres, compared with a bolus control 136 .…”
Section: Designing Spatial and Temporal Controlmentioning
confidence: 99%
“…Various materials have been explored for the formation of a local inflammatory niche to enhance immune responses 136 ; however, the impact of specific niche properties (for example, specific innate cell populations and/or their activation profiles) and the duration of niche persistence on downstream vaccine responses are poorly understood. Studies with self-assembled scaffolds based on silica rods have indicated that the local inflammatory niche must persist for at least 7 days to achieve prolonged antibody titres, compared with a bolus control 136 . By contrast, niches created by injectable hydrogels that persist for about 2–4 weeks lead to a more durable and higher-affinity humoral immune response than a bolus control 66 .…”
Section: Designing Spatial and Temporal Controlmentioning
confidence: 99%
“…72 Among various organic-or inorganic-based biomaterials, mesoporous silica-based vaccines represent a promising and versatile platform to present viral antigens, induce immune cell activation, and promote prolonged antibody production, as exemplified in the elegant work that highlights the development of mesoporous silica rod-based pore-forming platforms for in situ modulation of host immune cells as a vaccine against infectious diseases. 73 Soft biomaterials, including hydrogel scaffolds, can also offer a versatile platform to deliver a wide variety of therapeutics. High levels of biocompatibility, tunable physicochemical properties, controlled release, and tunable degradation profiles are among the promising characteristics of polymer-based hydrogels.…”
Section: Route Of Vaccine Administration and Targetingmentioning
confidence: 99%